Changing the course of history? Implementing water reforms in Ghana and South Africa - Wolfram Laube (University of Bonn, Center for Development Research (ZEF), 2009)
Many African countries have seen the passing of new water laws. Reflecting international discourses on IWRM, they put the use, management and value of water in an eco-systemic perspective, while they reflect the Dublin principles with regard to issues such as efficiency, sustainability, equity and the participation of stakeholders - particularly women. Nevertheless, within different ecological, economic and political contexts, these reforms develop different dynamics and outcomes. This article will discuss examples from Ghana and South Africa in order to show how the adoption and the implementation of water policies have to be understood as contextually embedded. Negotiation processes around water reforms are historically contingent and shaped by the particular political and economic history of a given country and the way resources have been negotiated and allocated within it. These patterns give little leeway for independent developments in the water sector. While the principles of IWRM have been adopted quite easily in Ghana and South Africa on the policy level, the process of their implementation, especially with regard to public participation in decision making processes is problematic because of contextual factors. While the implementation of general water sector policy is forestalled, neo-liberal economic principles of resource management and service provision are that largely shape the everyday politics of water are implemented, often without participative approaches, but with lively civic engagement.
Keywords: 330; Africa; water policy; political economy; IWRM; reform implementation